Leukemia Cutis in a Patient with Rare Indolent T-Prolymphocytic Leukemia - A Case Report and Review of the Literature. (28th October 2020) - Da Silva Lameira, F; Wang, K; Rinker, E; Jetly, R
Abstract: Introduction/Objective: T-cell prolymphocytic leukemia (T-PLL) is rare, comprising 2% of mature lymphocytic leukemias in adults. Clinical course is usually aggressive, however, 20-30% patients can have an indolent early phase. Most patients present with extensive disease with peripheral blood lymphocytosis, hepatosplenomegaly, and lymphadenopathy. T-PLL has a higher incidence in patients with ataxia-telangiectasia. Methods: We present a case of a 67-year old man with history of somatic mutation of ataxia-telangiectasia gene (ATM) and multiple malignancies, including melanoma, skin and laryngeal squamous cell carcinomas, adrenal adenoma and spindle cell lung tumor (diagnosed on biopsy), who developed leukemia cutis during an indolent phase of T-PLL. Results: Initial diagnosis of T-PLL was on routine complete blood count when patient had mild atypical lymphocytosis (5.5 x 109/L). Flow-cytometry immunophenotyping detected CD4 + 8 positive mature T-cells with no aberrant loss of T- cell antigens, and molecular studies confirmed clonal T-cell receptor beta and gamma gene rearrangements. T-PLL associated leukemia cutis was diagnosed on a leg skin nodule biopsy 10 months later. Subsequent bone marrow biopsy demonstrated low level involvement by T-PLL. The patient's T-PLL followed an indolent trajectory for three years and treatment was withheld until symptomatic presentation. Rapid disease progression was heralded with emergence of widespread T-PLL leukemia cutis, rapidly increasing lymphocytosis, extensive lymphadenopathy, splenomegaly and increasing LDH levels. Conclusion: Skin involvement is reportedly identified in 20% to 50% of T-PLL cases in some series. Skin manifestations can be heterogenous with a broad clinical differential. T-PLL associated leukemia cutis may not be recognized owing to the overall low incidence and in skin lesions appearing during an undiagnosed indolent early phase of T-PLL.We highlight the importance of accurate evaluation of non-specific skin lesions in early detection of T- PLL. Being aware of this diagnosis and early engagement in an interdisciplinary approach may allow for better outcomes of this aggressive malignancy.